Development of validation metrics using biorthogonal decomposition for the comparison of magnetic field measurements. (12th March 2015) - Victor, B S; Akcay, C; Hansen, C J; Jarboe, T R; Nelson, B A; Morgan, K D
Abstract: The Helicity Injected Torus-Steady Inductive (HIT-SI) injectors have been operated experimentally and simulated with a 3D pressureless Hall magnetohydrodynamic (MHD) code (NIMROD) at frequencies of 14.5, 36.8, 53.5 and 68.5 kHz. Simulations are compared to experimental data using biorthogonal decomposition (BD) of real and synthetic surface magnetic probe signals. First, the time-averaged magnetic field squared ( B 2 ), measured by the surface probes, is compared between experiment and simulation. Next, the spatial basis set from a reference shot is used to decompose other experimental and computational data sets. The output of the decomposition is compared back to the original basis set. This method reduces the comparison of the spatial distribution and time evolution of the magnetic signals to a single number. Finally, the modal distribution of the magnetic signals is compared using this data driven basis set.